Recommendations for reducing the effect of grain dust on the lungs. Canadian Thoracic Society Standards Committee. - Becklake, M (1996)
OBJECTIVE: To assess the appropriateness of the current Canadian standards for exposure to grain dust in the workplace. OPTIONS: The current permissible exposure limit of 10 mg of total grain dust per cubic metre of air (expressed as mg/m3) as an 8-hour time-weighted average exposure, or a lower permissible exposure limit. OUTCOMES: Acute symptoms of grain-dust exposure, such as cough, phlegm production, wheezing and dyspnea, similar chronic symptoms, and spirometric deficits revealing obstructive or restrictive disease. EVIDENCE: Articles published from 1924 to December 1993 were identified from Index Medicus and the bibliographies of pertinent articles. Subsequent articles published from 1994 (when the recommendations were approved by the Canadian Thoracic Society Standards Committee) to June 1996 were retrieved through a search of MEDLINE, and modification of the recommendations was not found to be necessary. Studies of interest were those that linked measurements of total grain dust levels to the development of acute and chronic respiratory symptoms and changes in lung function in exposed workers. Papers on the effects of grain dust on workers in feed mills were not included because other nutrients such as animal products may have been added to the grain. Unpublished reports (e.g., to Labour Canada) were included as sources of information. VALUES: A high value was placed on minimizing the biological harm that grain dust has on the lungs of grain workers. BENEFITS, HARMS AND COSTS: A permissible exposure limit of 5 mg/m3 would control the short-term effects of exposure to grain dust on workers. Evidence is insufficient to determine what level is needed to prevent long-term effects. The economic implications of implementing a lower permissible exposure limit have not been evaluated. RECOMMENDATIONS: The current Canadian standards for grain-dust exposure should be reviewed by Labour Canada and the grain industry. A permissible exposure level of 5 mg/m3 is recommended to control short-term effects. Further measurements that link the levels of exposure to respiratory health effects in workers across Canada should be collected to establish an exposure-response relation and possible regional differences in the effects of grain dust. VALIDATION: There has been no external review of these recommendations. However, the American Conference of Governmental Industrial Hygienists has recommended an 8-hour average exposure limit of 4 mg/m3 for wheat, oats and barley.